(untitled) (Acta Scientiarum. Animal Sciences, 2026)
Mammals’ self-cleaning behavior helps to reduce infestations of ectoparasites, especially ticks. We investigated the relationship between measurements of the filiform papillae of heifer tongues and tick infestation. To assess the papillae, biopsies were performed on the anterior surface of the tongues of 15 Holstein heifers. The samples were processed for evaluation by scanning electron microscopy. Statistical analysis was performed through a completely randomized design. The parameters studied were submitted to analysis of variance to determine the effect of infestation on the length and base width of the papillae, distance between bases and between tips, and number of papillae per unit area. Heifers with greater numbers of papillae (16.68 ± 3.30 cm2) and shorter filiform papillae (1.28 ± 0.35mm) had fewer ticks (P < 0.01) than heifers with fewer papillae (15.46 ± 1.91 cm2) and longer lengths (1.45 ± 0.39mm). We concluded that the morphology of the filiform papillae varies between cattle of the same breed and that the length and the number of papillae per unit area are related to tick infestation.